Study of the Effectiveness of Implementing Occupational Safety and Health with the Hazop Method in the Cikarang Industrial Center - Edwina Rudyarti (Formosa Publisher, 2022)
The brick industry center in Cikarang has not implemented Occupational Safety and Health (K3). This is due to the lack of understanding of industrial owners and workers regarding the importance of implementing OSH in the workplace. Therefore, the application of OSH in IKM, especially in the Cikarang industrial center, must be effective and optimal to increase the productivity and competitiveness of the industrial center. The purpose of this study was to assess the application of occupational safety and health with the HAZOP method in the Cikarang Brick Industry Center. This research is a quantitative research with a descriptive analytic design. The research objects are four brick industries in the Cikarang brick industry center. The stages in this research are hazard identification and risk assessment in industrial centers using the HAZOP method for potential work accident hazards. The results of this study obtained the findings of several risks with an extreme risk level of 17% with 3 very risky sources of danger, for high risk of 66% with 14 sources of high hazard, and a moderate risk of 17% with 3 sources of low hazard. The conclusion of this study is that there are 20 potential hazards that can occur with high risk potential or high risk which has the most potential with a total of 14 sources of danger.